Racial/ethnic disparities in hepatocellular carcinoma incidence and mortality rates in the United States, 1992–2018. Issue 3 (22nd April 2022) - Alvarez, Christian S.; Petrick, Jessica L.; Parisi, Dominick; McMahon, Brian J.; Graubard, Barry I.; McGlynn, Katherine A.
Abstract: Background and Aims: HCC is characterized by racial/ethnic disparities in rates. Recent USA reports suggest that incidence has begun to decline, but it is not clear whether the declines have occurred among all groups, nor whether mortality has declined. Thus, the current study examined USA incidence and mortality between 1992 and 2018. Approach & Results: HCC incidence and incidence‐based mortality data from the Surveillance, Epidemiology, and End Results program were used to calculate age‐standardized rates by race/ethnicity, sex, and age. Trends were analyzed using joinpoint regression to estimate annual percent change (APC). Age‐period‐cohort models assessed the effects on trends of age, calendar period, and birth cohort. Overall, HCC incidence significantly declined between 2015 and 2018 (APC, −5.6%). Whereas most groups experienced incidence declines, the trends were most evident among Asians/Pacific Islanders, women, and persons <50 years old. Exceptions were the rates among non‐Hispanic Black persons, which did not significantly decline (APC, −0.7), and among American Indians/Alaska Natives, which significantly increased (APC, +4.3%). Age‐period‐cohort modeling found that birth cohort had a greater effect on rates than calendar period. Among the baby boom cohorts, the 1950–1954 cohort had the highest rates. Similar to the overall incidence decline, HCC mortality rates declined between 2013 and 2018 (APC, −2.2%). Conclusions: HCC incidence and mortality rates began to decline for most groups in 2015, but persistent differences in rates continued to exist. Rates among non‐Hispanic Black persons did not decline significantly, and rates among American Indians/Alaska Natives significantly increased, suggesting that greater effort is needed to reduce the HCC burden among these vulnerable groups. Abstract : Age‐adjusted rates per 100, 000 person‐years overall and by race/ethnicity of HCC incidence (left) and mortality (right) in the USA, 1992‐2018. AIAN, American Indian/Alaska Native; API, Asian/Pacific Islander; NHB, non‐Hispanic Black; NHW, non‐Hispanic White.